In silico analysis of alternative splicing events implicated in intracellular trafficking during B-lymphocyte differentiation - Ostwaldt, Felix; Los, Bruna; Heyd, Florian (Frontiers in Immunology, 2022)
There are multiple regulatory layers that control intracellular trafficking and protein secretion, ranging from transcriptional to posttranslational mechanisms. Finely regulated trafficking and secretion is especially important for lymphocytes during activation and differentiation, as the quantity of secretory cargo increases once the activated cells start to produce and secrete large amounts of cytokines, cytotoxins, or antibodies. However, how the secretory machinery dynamically adapts its efficiency and specificity in general and specifically in lymphocytes remains incompletely understood. Here we present a systematic bioinformatics analysis to address RNA-based mechanisms that control intracellular trafficking and protein secretion during B-lymphocyte activation, and differentiation, with a focus on alternative splicing. Our in silico analyses suggest that alternative splicing has a substantial impact on the dynamic adaptation of intracellular traffic and protein secretion in different B cell subtypes, pointing to another regulatory layer to the control of lymphocyte function during activation and differentiation. Furthermore, we suggest that NERF/ELF2 controls the expression of some COPII-related genes in a cell type-specific manner. In addition, T cells and B cells appear to use different adaptive strategies to adjust their secretory machineries during the generation of effector and memory cells, with antibody secreting B cell specifically increasing the expression of components of the early secretory pathway. Together, our data provide hypotheses how cell type-specific regulation of the trafficking machinery during immune cell activation and differentiation is controlled that can now be tested in wet lab experiments.